The Mamluk–Nusantara Nexus in Spice, Faith and Diplomacy - Kurniawan Arif Maspul; Muhammad Fakhry Hanif; Hasbi Yusron (Indonesian Journal Publisher, 2026)
This study investigates the Mamluk–Nusantara nexus (13th–early 16th centuries), a remarkable instance of pre-modern, non-coercive trans-civilizational influence spanning the Indian Ocean. While the Mamluk Sultanate of Egypt and Syria never projected military power beyond Aden, its symbolic revival of the Abbasid caliphate, guardianship of Mecca and Medina, and monopolistic control over the spice trade generated profound ideational attraction in the Malay Archipelago. Employing a qualitative multiple-case-study design and process-tracing methodology, the research draws on Ibn Battuta’s Rihla, Mamluk chancery documents, Jawi manuscripts, and local chronicles to test four hypotheses rooted in constructivist, network, world-systems, and soft-power theories. The analysis reveals that shared Shafi‘i jurisprudence, trust-based Karimi and Hadrami merchant networks, educational pilgrimages to Al-Azhar, and the adoption of Jawi script functioned as conduits for a peaceful, syncretic Islamisation that birthed the tolerant Islam in Nusantara. This multi-causal model challenges realist assumptions by demonstrating that caliphal legitimacy and cultural affinity, not coercion, drove diplomatic alignment and identity formation across 5,000 miles. The findings offer a historical template for contemporary cultural diplomacy, halal trade corridors, and inter-civilisational cooperation, underscoring the enduring relevance of the spice-scented bridge between Cairo and the Archipelago.